Selection of the optimal medical waste incineration facility location: A challenge of medical waste risk management - Stanojević, Kristina; Radovanović, Goran; Makajić-Nikolić, Dragana; Savić, Gordana; Simeunović, Barbara; Petrović, Nataša (Vojnosanitetski pregled, 2022)
Background/Aim. Among the other challenges of the 21st century, medical waste (MW) has become an arising problem for both the environment and people because of its increasing amount, variety, and complexity. That is way MW management has become one of the very important ecological imperatives. Serbia with no potential for appropriate disposal of all MW is forced to export MW to countries with MW incineration facilities. Incineration lowers the possible risks of inappropriate disposal and the emission of environmental pollutants, but leads to the need for a “clever” choice of the incinerator facility location which has to meet diverse environmental, economic and technical criteria Methods. The criteria for the choice of optimal locations for a MW incinerator facility were as follows: the amount of MW that needs to be transported, the transport time from other locations, the current pollution of the location, the unemployment rate and the location safety in terms of natural disasters and accidents. By using the obtained results for seven efficient locations gained by Data Envelopment Analysis (DEA), we used a goal programming for the analysis of the most suitable location for a MW incineration facility. Results. In the proposed methodology on the chosen scenario and analysing the criteria relevant for selecting the most suitable location, using the DEA method, seven efficient locations for MW incineration facility were obtained. The optimal location was location 13. Conclusion. Based on the obtained results, we demonstrated that by the use of goal programming it is possible to develop a methodology for selection of optimal MW incineration facility location as one of the necessary activities of MW risk management.
Keywords: environment; incineration; medical waste; medical waste disposal; risk control